Thames groundwater scheme proceedings of the conference held at Reading University on 12-13 April, 1978 - Burt, Anthony M. (Institution of Civil Engineers, 1978)
Following an opening address by Lord Nugent of Guildford, these papers discuss concept to commissioning, characteristics and yield in fissured chalk, commissioning and operation, and conclude by looking at the archaeological aspects of the Thames Groundwater Scheme.